SISTEM MANEJEMEN PENJUALAN TOKO OMEGA BERBASIS WEB - habibi, habibi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Omega is a specialty food distributor shop, namely Getas which is located in Belitung. Manual buying and selling activities and marketing and promotions are still limited for that we need an information system that can expand marketing and facilitate transactions, making it more efficient, fast and easy without being hindered by distance and time. There really needs to be convenience in service to make it easier for customers who are far from reach. The purpose of this research is to build a web-based omega store sales information and management system. For this reason, a web-based omge sales system was created, known as E-commerce (Electronic Commer). This application makes it easier for customers to buy products in the Omega store online anytime and anywhere without taking time and customers can also find out what products are available at the Omega store. The use of the website is expected to expand the reach of product marketing without being limited by time so that it can increase sales